(untitled) (Journal of Telenursing (JOTING), 2025)
This study aims to determine the effect of a combination of deep breathing relaxation methods, 5-7-8, and dhikr on stress and blood pressure of hypertension patients in the Krucil Health Center work area, Probolinggo Regency. The research method used a quasi-experiment with a population of 161 people, using a purposive sampling technique, which obtained a sample of 115 people with logistic regression test analysis. The results of this study were obtained before the intervention; all respondents experienced severe to very severe stress. After the intervention, stress levels decreased significantly to mild and moderate stress. Blood pressure also reduced considerably, from hypertension to 87.8% pre-hypertension and 12.2% normal. Logistic regression analysis showed that this intervention significantly reduced stress (p = 0.012), with an increase in the likelihood of experiencing moderate stress by 2.667 times if the initial stress was high. This model explains 7.1% of post-intervention stress variability and has a classification accuracy of 60.9%. However, there was no significant effect between blood pressure before and after the intervention (p = 0.429), with the contribution of independent variables to the results being very small (Nagelkerke R Square 0.011). In conclusion, combining deep breathing relaxation in the 5-7-8 method and dhikr effectively reduces stress levels in hypertension patients, although the effect on blood pressure is not statistically significant. This approach can be used as an alternative, complementary therapy in the treatment of hypertension based on spirituality and relaxation. Keywords: Dhikr, Hypertension, Non-Pharmacological Intervention, 5-7-8 Breath Relaxation, Stress, Blood Pressure